2014
DOI: 10.1155/2014/453237
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Correlation between Appointment Scheduling and Patient Satisfaction in a Pediatric Dental Setup

Abstract: Introduction. The practice of modern pediatric dentistry requires delivery of quality care in combination with adherence to excellent business as well as time management principles. A definite appointment schedule should be presented to the parents on the first or second appointment. More importantly, the prescribed schedule should be followed to the best of the professional abilities of the pediatric dentist. Aims. The aim of the study was to assess the co-relation between appointment scheduling and patient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Even though caregivers are favorably disposed towards caring for the elderly relatively [ 28 , 29 ], institutional care is still largely a rejected phenomenon [ 29 ] in most African settings, which is corroborated by our study findings. The acknowledgement of appointment scheduling to follow up cases is encouraging, as appointment scheduling has been identified to lie at the intersection of timely access to health care services and efficiency [ 30 ]. Agada and colleagues (2015) substantiate the realization and adoption on the need for effective appointment scheduling by advocating for a mixed block appointment rather than existing single block appointment systems [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though caregivers are favorably disposed towards caring for the elderly relatively [ 28 , 29 ], institutional care is still largely a rejected phenomenon [ 29 ] in most African settings, which is corroborated by our study findings. The acknowledgement of appointment scheduling to follow up cases is encouraging, as appointment scheduling has been identified to lie at the intersection of timely access to health care services and efficiency [ 30 ]. Agada and colleagues (2015) substantiate the realization and adoption on the need for effective appointment scheduling by advocating for a mixed block appointment rather than existing single block appointment systems [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that the most important reason for attending these clinics is low cost of service. [23242526]…”
Section: Discussionmentioning
confidence: 99%
“…A strong inverse relationship between patient satisfaction and waiting time has been also demonstrated by many studies. [49][50][51][52] Therefore, there was room for improvement for referral patients as well as in the dual-referral system. Which makes it possible for doctors to spend more energy on patients to improve their experience.…”
Section: Discussionmentioning
confidence: 99%